Growth pattern of crossbred cattle under homoscedstic and heteroscedastic error variance condition - SINGH, SURENDRA; BHAR, L M; PAUL, A K (The Indian Journal of Animal Sciences, 2011)
Different growth models are fitted in growth data for FriesianxSahiwal breed atAgra station. Gompertzmodel gave better fit than Logistic modeL The GLS estimates are found to be more precise than OLS estimates for both Logistic as well as Gompertz model under heteroscedastic error condition.Â